Mineral processing technology : an introduction to the practical aspects of ore treatment and mineral recovery - Wills, B. A. (Barry Alan) (International series on materials science & technology., 1992)
Provides practising engineers and students of mineral processing, metallurgy and mining with a review of the common ore-processing techniques utilized in modern installations. Each chapter encompasses all the recent technical developments within each field, and discusses new equipment and process routes. This latest edition has been thoroughly revised and updated to include important new sections on economics, use of computers and developments in froth flotation. A further feature is a valuable collection of microcomputer programs, written in ANSI BASIC, for the solution of numerical mineral processing problems. The work is fully referenced up to 1987, indexed, and SI units are used throughout.